Faktor-Faktor Yang Mempengaruhi Kepatuhan Dokter Dalam Mengisi Rekam Medis Di Unit Rawat Inap Rumah Sakit Wava Husada - Indrawan, Doby (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
The hospital is a public organization that consists of several person with their scientific competences , that is hoped to give a qualified health service to the people. The qualified health service has to be able to give clear information about what, who, when, where and how the health service will be done or had done in form of eligible medical record by the doctors and other medical persons.The study was done by survey method for three weeks onÂ 26 respondents (general doctors and specialist) who give health service in Wava Husada Hospital Care Unit, Kepanjen. The data collecting technique is using questionaires. The data analysis methods with brainstorming and Literature Review.26 questionaires were fulfilled completely; there are doctorâ€™s character according to age, 30% is between 25-34 years old, 25% is 45-54 years old and 20% is 55-64 years old. According to the gender, there are 80% men and 20% women. According to their competences, 20% general doctors and 80% are specialists. According to the work experience in Wava Husada Hospital, there are 48% respondent have worked for 0-5 years, 52% have worked for 6-10 years. The attitude aspects of doctor is founded to be in hurry (40%),unwilling to give their time (5%) and have ever reminded their colleague to fulfill the medical record (20%). The medical record form aspects, the doctors still thinks that the medical record for is not appropriate (15%), several doctors thinks that the working place is not comfortable (15%), have not been given feedbacks (10%) and the order to fulfll the medical report (20%). There are also found during the survey, several willings of the doctors about the medical record to be fulfilled completely according to Minimum Service Standard.Completing medical record is affected by the doctorsâ€™ attitude towards the records, the form of the medical record and the medical record person as the service agent of medical record in the hospital. It is needed a good collaboration and synergy between the medical record person, the nurses and the doctors in order to increase the medical records completing number.